Sequelae of Posthemorrhagic Hydrocephalus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The neurologic and developmental outcome of 33 low birth weight neonates with ventriculomegaly and in 39 with no ventriculomegaly after hemorrhage were evaluated prospectively in the Departments of Pediatrics and Neurosurgery, Wayne State University School of Medicine and Children's Hospital of Michigan, Detroit.